Sharia Compliance on Murabaha Financing in Sharia Rural Banks: A Review of Recent Practices - Muhammad Khaeruddin Hamsin; Abdul Halim; Rizaldy Anggriawan; Ahmad Fanani (Varia Justicia, 2022)
One of the most significant concerns in the practice of Sharia Rural Banks is Islamic compliance. This is necessary to guarantee that the policies, provisions, processes, and procedures, as well as the Sharia Rural Bank’s (BPRS) business activities, are in accordance with the provisions and Sharia Principles. The aim in this paper is to extensively evaluate whether Sharia rural banks have completely implemented and conformed with Sharia norms and values, particularly when it comes to Murabaha financing practices. It elaborates on the compliance assessment from the initial application of Murabaha to its complete execution. It also explores the BPRS debt settlement plan, which is in accordance with the DSN-MUI Fatwa, and discusses the OJK Policy on the restructuring process during the Covid-19 crisis. The paper used a normative-empirical research method with employing statutory and conceptual approaches. The análysis of data is described in qualitative-descriptive where the data was obtained from library and empirical research. The findings show that, with a few outliers, the DSN-MUI Fatwa and OJK Policy are implemented in the execution of Murabaha contracts at BPRS. Even during a pandemic crisis, when many customers were unable to settle their debts, the bank was compelled to postpone the debt while still adhering to Sharia principles. However, certain features, particularly the application of the Murabaha contract that is preceded by a wakalah contract, are thought to be in contradiction of the DSN-MUI fatwa on Murabaha.